Determinants of Poor Health among Workers in Criminal Justice, Community and Social Services, and Healthcare: Adverse Childhood Experiences, Workplace Trauma Exposure, and Gender Differences - Knight, Kelly E. (Women & criminal justice, 2024)
Adverse childhood experiences and workplace trauma exposure are associated with poor health. However, their differential impacts by gender are difficult to assess in studies of organizations with gender imbalances (e.g., law enforcement officers are more likely men whereas social workers are more likely women). Using a community-based participatory research framework, this study examines trauma exposure, mental and physical health, and substance use in an occupationally diverse sample (n = 391). Trauma exposure was high and associated with poor health. Even though women experienced more adversity, they were often more resilient than men. Implications for trauma-informed workplaces are discussed.